2017
DOI: 10.1371/journal.pone.0172356
|View full text |Cite
|
Sign up to set email alerts
|

4D-CTA improves diagnostic certainty and accuracy in the detection of proximal intracranial anterior circulation occlusion in acute ischemic stroke

Abstract: IntroductionIn acute ischemic stroke, imaging of the cranio-cervical vessels is essential for intra-arterial treatment selection. Fast, reliable and easy accessible imaging is necessary 24 hours a day, 7 days a week. Radiologists in training and non-expert readers often perform initial reviewing. In this pilot study, the potential benefit of adding 4Dimensional-CT Angiography (4D-CTA) to the patient selection protocol for intra-arterial therapy is investigated.Materials and methodsTwenty-five datasets of prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In general, experienced (neuro)radiologists are well-capable of identifying LVOs on CTA, enabling prompt diagnosis of acute ischemic stroke due to LVO. 4 5 Yet, such expertise is not always readily available, for instance in hospitals with lower caseloads and during off-hours when dedicated neuroradiologists are not on call. This may hamper fast and accurate CTA assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In general, experienced (neuro)radiologists are well-capable of identifying LVOs on CTA, enabling prompt diagnosis of acute ischemic stroke due to LVO. 4 5 Yet, such expertise is not always readily available, for instance in hospitals with lower caseloads and during off-hours when dedicated neuroradiologists are not on call. This may hamper fast and accurate CTA assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 4D-CTA/CTP provides more accurate images of the arterial, arteriovenous, venous, and late venous phases based on perfusion time–density curves, and does not additionally increase the radiation dose. This multi-phase dynamic CTA evaluation of collateral flow has a high temporal resolution and a smoother baseline between patients, providing reliable original data for collateral circulation evaluation, enabling a complete assessment of collateral circulation [ 18 ] and improving diagnostic accuracy [ 19 ], as well as providing value in determining clinical prognosis [ 12 ]. Second, a residual convolutional neural network [ 20 ] was employed, which can improve the performance of image classification tasks while deepening the network.…”
Section: Discussionmentioning
confidence: 99%
“…4D CTA combined with CTP imaging feature analysis can provide changes in cerebral vascular morphology in cerebral stroke. Wagemans et al [ 26 ] showed that 4D CTA improved the diagnostic accuracy of proximal intracranial anterior circulation occlusion in acute stroke. 4D CTA, used as an additive to conventional CTA and CTP in patients with AIS eligible for intraarterial therapy, showed a tendency to increase diagnostic accuracy and improve diagnostic certainty when reviewed by radiologists in training, while only slightly extending the time to diagnosis.…”
Section: Discussionmentioning
confidence: 99%